2017
DOI: 10.1038/s41598-017-15022-3
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-inflammatory and anti-fibrotic effects of intravenous adipose-derived stem cell transplantation in a mouse model of bleomycin-induced interstitial pneumonia

Abstract: Adipose-derived stem cells (AdSCs) have recently been considered a useful treatment tool for autoimmune disease because of their anti-inflammatory and immunosuppressive effects. We investigated the therapeutic effect of intravenous AdSC transplantation in a mouse model of bleomycin-induced lung injury. AdSCs accumulated in the pulmonary interstitium and inhibited both inflammation and fibrosis in the lung, markedly improving the survival rate of mice with bleomycin-induced lung injury in a cell number-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 40 publications
1
55
0
1
Order By: Relevance
“…It would be more appropriate to use human ADSCs from a clinical perspective. However, previous studies on ADSCs have demonstrated their effectiveness across several species [33][34][35] . Second, the severity of RA in our mouse model was evaluated on the basis of generalized clinical scoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be more appropriate to use human ADSCs from a clinical perspective. However, previous studies on ADSCs have demonstrated their effectiveness across several species [33][34][35] . Second, the severity of RA in our mouse model was evaluated on the basis of generalized clinical scoring.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue was harvested from the inguinal region and used in all experiments as subcutaneous white adipose tissue. ADSCs were isolated from adipose tissue based on a previously described procedure 37 with slight modifications 35,38 . Briefly, adipose tissue harvested from mice subcutaneous area was washed in PBS, minced, and digested in 5 mL of type VIII collagenase (1 mg/mL in 1% BSA/HBSS; Life Technologies Japan, Tokyo, Japan) for 40 min at 37 °C using a Bioshaker BR15 (TAITEC, Tokyo, Japan) in accordance with the manufacturer's instructions.…”
Section: Harvesting Of Adipose Tissue and Adipose Stem Cell Isolationmentioning
confidence: 99%
“…Adipose‐tissue‐derived stromal/stem cells are attracting much interest because they are pluripotent somatic stem cells capable of repairing an impaired organ, not only because of their ability to differentiate into miscellaneous cell types but also because of their ability to modulate inflammation, which is harmful to organs. The immunomodulatory effects of ADSCs are attractive, as the consequences are favorable in suppressing inflammation . Miscellaneous etiologies of chronic liver diseases, such as hepatitis B or hepatitis C infection, autoimmune hepatitis, and primary biliary cholangitis, are well known, and the immunopathological features differ among these etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory effects of ADSCs are attractive, as the consequences are favorable in suppressing inflammation. 28 Miscellaneous etiologies of chronic liver diseases, such as hepatitis B or hepatitis C infection, autoimmune hepatitis, and primary biliary cholangitis, are well known, and the immunopathological features differ among these etiologies. The current study sheds light on the role of IL-17 in the development of NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose-mesenchymal stem cells have also been evaluated in some interesting studies [ 20 , 21 , 22 ]. Thashiro and colleagues studied the differences between young or old donor adipose-MSCs in old mice after 24 h of BLM instillation [ 20 ].…”
Section: Preclinical Experiencesmentioning
confidence: 99%